2021
DOI: 10.1101/2021.02.09.430385
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The anterior Hox geneceh-13andelt-1/GATAactivate the posterior Hox genesnob-1andphp-3to specify posterior lineages in theC. elegansembryo

Abstract: Hox transcription factors play a conserved role in specifying positional identity during animal development, with posterior Hox genes typically repressing the expression of more anterior Hox genes. Here, we dissect the regulation of the posterior Hox genes nob-1 and php-3 in the nematode C. elegans. We show that nob-1 and php-3 are co-expressed in gastrulation-stage embryos in cells that previously expressed the anterior Hox gene ceh-13. This expression is controlled by several partially redundant transcriptio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 72 publications
2
2
1
Order By: Relevance
“…In contrast with our observation that TBX418 concatemers are sufficient to drive anterior-biased [52,[60][61][62][63][64]. Additionally, we observe modularity within the -3.9 kb enhancer, with three non-overlapping regions of the enhancer each sufficient to drive anteriorbiased expression.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast with our observation that TBX418 concatemers are sufficient to drive anterior-biased [52,[60][61][62][63][64]. Additionally, we observe modularity within the -3.9 kb enhancer, with three non-overlapping regions of the enhancer each sufficient to drive anteriorbiased expression.…”
Section: Discussioncontrasting
confidence: 99%
“…We found that the predicted enhancers in the promoter region of ref-2 function modularly, such that each enhancer drives different expression patterns, presumably providing multiple inputs to fine-tune the expression pattern of ref-2 . Combined with other recent studies this adds to evidence that enhancer-mediated regulation is widespread during C. elegans embryonic development [54,65–69]. Additionally, we observe modularity within the −3.9 kb enhancer, with three non-overlapping regions of the enhancer each sufficient to drive anterior-biased expression.…”
Section: Discussionsupporting
confidence: 84%
“…We found that the predicted enhancers in the promoter region of ref-2 function modularly, such that each enhancer drives different expression patterns, presumably providing multiple inputs to fine-tune the expression pattern of ref-2. Combined with other recent studies this adds to evidence that enhancer-mediated regulation is widespread during C. elegans embryonic development [52,[63][64][65][66][67]. Additionally, we observe modularity within the -3.9 kb enhancer, with three non-overlapping regions of the enhancer each sufficient to drive anteriorbiased expression.…”
Section: Concatemerized Tbx Sites Are Sufficient To Drive Anterior-sp...supporting
confidence: 84%
“…We fused each putative enhancer to a reporter cassette consisting of a minimal pes-10 promoter and a his-24::mCherry reporter. The pes-10 promoter is widely used, drives no consistent embryonic expression on its own [13,51,52] and is compatible with a wide variety of enhancers [13,51]. We introduced each reporter into worms and used StarryNite to determine in which cells each putative enhancer drives expression.…”
Section: Modular Enhancers Control Ref-2 Embryonic Expressionmentioning
confidence: 99%
See 1 more Smart Citation